Investment and Inequality in Africa: which financial channels are good for the poor? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
This paper examines how domestic, foreign, private and public investments affect income-inequality through financial intermediary dynamics. With the exception of financial allocation efficiency, financial channels of depth and activity are good for the poor as they diminish estimated household income-inequality. Financial size does not have a significant income-redistributive effect. Financial efficiency has a disequalizing effect, implying policies designed to improve the allocation of mobilized funds only benefit the rich to the detriment of the poor. The use of financial and investment dimensions previously missing in the literature provide new insights into the finance-inequality nexus. Policy implications are discussed.
Keywords: D60; E25; G20; I30; O55; 330; Finance; Investment; Poverty; Inequality; Africa